Hierarchical Structures Incorporating Carbon and Zeolite to Remove Radioactive Contamination - Al-Rahmani, Altaf A.; Al-Attafi, Shireen K.; Al-Nasri, Salam K.; Jasim, Zuhair W. (Iraqi journal of science, 2020)
Synthesis, characterization and application of hierarchical zeolites are becoming a subject of an increasing interest among scientists and researchers. Hierarchical structures incorporating zeolites   possess secondary porosity at meso- and macrolevel to overcome problem of mass transport, which occurs with using conventional zeolites. In this study, the porous carbon surface was prepared by carbonization of the locally available agricultural waste of the Iraqi Nut shell (NS) using a carbonization method in a tubular furnace at 900ËšC for two hours. Hierarchicalpours structures including zeolite were prepared by the mechanical activation of the carbon surface using ultrasonication with a nanoparticles suspension of ground commercial zeolite type 4A. Zeolite was milled using 0.3-0.4 mm diameter glass balls as grinding media to prepare nanoparticles seeding, which increases the crystallization of the amorphous aluminosilica gel on the modified carbon surface during the hydrothermal method. The Product of the syntheses of zeolite 4A and the hierarchal composite material were characterized using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Nitrogen-Adsorption /desorption isotherms (BET), Energy Dispersive Spectroscopy (EDX), and Thermo Gravimetric Analysis (TGA) to determine the structure, morphology, surface area, chemical composition, and percentage weight of zeolite on carbon, respectively. The products were applied to remove the radioactive hazardous cesium isotope Cs137 from the radioactive wastewater provided by the destroyed building of Radiochemistry laboratories (RCL) in AL-Tuwaitha Nuclear Site. Gamma spectroscopy system with high purity germanium detector (HPGe) was used to measure the activity concentration for the contamination water before and after the treatment. The results showed that the activity concentration decreased from 4800 Bq/L to 186Bq/L and 100Bq/L using pure zeolite 4A and NSZ.respectively. The results also showed that the composite materials could be used effectively to remove radioactive 137Cs from a real wastewater, with ease of separation and recovery from the solution compared with  the pure zeolite 4A.